2016
DOI: 10.1097/adt.0000000000000081
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Styles and Psychological Correlates in a Sample of Egyptian Adolescents With Substance-use Disorders

Abstract: Objectives:To study parenting styles and psychological correlates among a group of Egyptian adolescents with substance-use disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Overall, we found 7 records reporting on the association between depressive symptoms and risky sexual behavior, [44][45][46][47][48][49][50] 10 for substance use, 45,48,49,[51][52][53][54][55][56][57] 4 for delinquency, [58][59][60][61] 3 for self-harm [62][63][64] and 11 for suicidal behavior (2 of which were included in the systematic review). [65][66][67][68][69][70][71][72][73][74][75] Three studies reported on both risky sexual behavior and substance use, separately.…”
Section: [Insert Figure 1 Around Here]mentioning
confidence: 99%
“…Overall, we found 7 records reporting on the association between depressive symptoms and risky sexual behavior, [44][45][46][47][48][49][50] 10 for substance use, 45,48,49,[51][52][53][54][55][56][57] 4 for delinquency, [58][59][60][61] 3 for self-harm [62][63][64] and 11 for suicidal behavior (2 of which were included in the systematic review). [65][66][67][68][69][70][71][72][73][74][75] Three studies reported on both risky sexual behavior and substance use, separately.…”
Section: [Insert Figure 1 Around Here]mentioning
confidence: 99%